Structure-Property Correlation in Additively Manufactured High-Temperature Materials: Insights from Nickel-Based Superalloy IN718 & Nickel-Based Eutectic High Entropy Alloy AlCoCrFeNi2.1 - Vikram, Raja Jothi; Suwas, Satyam advised (Bangalore IISc, 2023)
High-temperature alloys are technically very important materials that possess higher resistance toward mechanical and chemical degradation at 0.4-0.6 TM for a constant/cyclic load. These attributes make them candidate materials for aerospace and energy generation systems that require harsh operating conditions. The most popularly used high-temperature alloys are the Nickel-base superalloys, and among various Ni-base alloys, Inconel 718 (IN 718) is the most used material. The currently used superalloys are already exploited to very high operating temperatures near their solidus or the precipitate solvus temperatures. Any further increase in Carnot efficiency is only possible through design improvements and enhanced turbine cooling efficiency, which the Additive Manufacturing (AM) technique can address. However, the adoption of AM processes for aerospace/mission-critical components is impeded due to microstructural heterogeneities and spontaneous defects observed in AM-produced parts. It is, therefore, necessary to develop processes that head to minimum porosity and design suitable heat treatments, and to evaluate the relevant mechanical properties post-heat treatment.
Include bibliographical references and index
PhD; 2023; Materials engineering
Keywords: Additive Manufacturing; Mechanical behavior; Superalloys; High Entropy Alloys; Nickel-base superalloys